MicroRNA-15a-5p serves as a potential biomarker and regulates the viability and apoptosis of hippocampus neuron in children with temporal lobe epilepsy - Na Li; Jingmei Pan; Wei Liu; Yuanyuan Li; Feng Li; Min Liu (BMC, 2020)
Abstract Background Temporal lobe epilepsy (TLE) is the most common type of epilepsy, usually starting in childhood. The dysregulation of microRNAs (miRNAs) has been identified in neurological disorders. The current study investigated the expression level and clinical significance of miR-15a-5p in TLE children, and explored its function in regulating cell behaviors of hippocampal neurons. Methods The expression level of miR-15a-5p was examined in the serum of 63 TLE children. Primary hippocampal cells were cultured in magnesium-free medium to mimic TLE condition in children. The effect of miR-15a-5p on the viability and apoptosis of hippocampus neuron was assessed using MTT or flow cytometric apoptosis assay. Results TLE children had significantly low expression of miR-15a-5p. MiR-15a-5p was of great value for the diagnosis of TLE in children, with high specificity and sensitivity. The expression level of miR-15a-5p was decreased significantly in hippocampal cells treated in the magnesium-free medium. Overexpression of miR-15a-5p attenuated TLE-induced reduction for cell viability, and reversed the cell apoptosis induced by TLE. Conclusions MiR-15a-5p is downregulated in children with TLE, and overexpression of miR-15a-5p promoted the viability and inhibited the apoptosis of hippocampal neuron. MiR-15a-5p may be a promising biomarker for the diagnosis of children TLE.